Cam Deformities and Limited Hip Range of Motion Are Associated With Early Osteoarthritic Changes in Adolescent Athletes: A Prospective Matched Cohort Study. (November 2017) - Wyles, Cody C.; Norambuena, Germán A.; Howe, Benjamin M.; Larson, Dirk R.; Levy, Bruce A.; Yuan, Brandon J.; Trousdale, Robert T.; Sierra, Rafael J.
Background: The natural history of femoroacetabular impingement (FAI) remains incompletely understood. In particular, there is limited documentation of joint damage in adolescent patients with limited range of motion (LROM) of the hip, which is commonly associated with FAI. Purpose: To evaluate changes in magnetic resonance imaging (MRI), radiographs, and clinical examinations over 5 years in a group of athletes from a wide variety of sports with asymptomatic LROM of the hip compared with matched controls. Study Design: Cohort study (prognosis); Level of evidence, 2. Methods: The authors screened 226 male and female athletes aged 12 to 18 years presenting for preparticipation sports physical examinations. Using a goniometer, we identified 13 participants with at least one hip having internal rotation <10° with the hip flexed to 90°. Overall, 21 of 26 hips (81%) had internal rotation <10°. These participants were age- and sex-matched to 13 controls with internal rotation >10°. At the time of enrollment, all participants were asymptomatic and underwent a complete hip examination and radiographic imaging with radiographs (anteroposterior [AP] and von Rosen views) and non-arthrogram MRI. Participants returned at 5-year follow-up and underwent repeat hip examinations, imaging (AP and lateral radiographs and non-arthrogram MRI), and hip function questionnaires. MRI scans were classified as "normal" versus "abnormal" based on the presence of any of 13 scored chondral, labral, or osseous abnormalities. Comparisons between the LROM group and control group were performed using generalized linear models (either linear, logistic, or log-binomial regression as appropriate for the outcome) with generalized estimating equations to account for the within-participant correlation due to patients having both hips included. Relative risk (RR) estimates are reported with 95% CIs. Results: At the time of study enrollment, 16 of 26 hips (62%) in the LROM group had abnormal MRI findings within the acetabular labrum or cartilage compared with 8 of 26 hips (31%) in the control group (RR, 2.0; 95% CI, 0.95-4.2; P = .067). The mean alpha angle measured from radial MRI sequences was 58° in the LROM group versus 44° in the control group ( P < .0001). In the LROM group, 13 of 26 hips (50%) had a positive anterior impingement sign, whereas 0 of 26 hips (0%) had a positive anterior impingement sign in the control group. At 5-year follow-up, 18 of 19 hips (95%) in the LROM group had abnormal MRI findings compared with 14 of 26 hips (54%) in the control group (RR, 1.7; 95% CI, 1.1-2.7; P = .014). New or progressive findings were documented on MRI in 15 of 20 hips in the LROM group compared with 8 of 26 hips in the control group (RR, 2.4; 95% CI, 1.2-4.8; P = .011). Six of 22 hips (27%) in the LROM group progressed from Tönnis grade 0 to Tönnis grade 1 in degenerative changes, whereas all 26 hips in the control group remained at Tönnis grade 0 on hip radiographs. In the LROM group, 11 of 22 hips (50%) had a positive anterior impingement sign, whereas 1 of 26 hips (4%) had a positive anterior impingement sign in the control group. A cam deformity (alpha angle >55° on lateral radiographs) was present in 20 of 22 hips (91%) in the LROM group and 12 of 26 hips (46%) in the control group ( P = .0165). The following variables at baseline were associated with an increased risk of degenerative changes at 5-year follow-up for the entire cohort: decreased hip internal rotation, positive anterior impingement sign, decreased hip flexion, increased alpha angle, and presence of a cam lesion. Conclusion: At 5 years, young athletes with LROM of the hip showed increased progressive degenerative changes on MRI and radiographs compared with matched controls. Although the majority of these participants remained asymptomatic, those with features of FAI had radiographic findings consistent with early osteoarthritis. These outcomes suggest that more aggressive screening and counseling of young active patients may be helpful to prevent hip osteoarthritis in those with FAI.